PENGARUH KUALITAS PELAYANAN, KETEPATAN WAKTU PELAYANAN DAN KENYAMANAN LINGKUNGAN TERHADAP KEPUASAN PASIEN MELALUI KEPERCAYAAN PASIEN RAWAT INAP DI RSUD ASEMBAGUS SEBAGAI VARIABEL INTERVENING - Yan Parta Wijaya; Siti Soeliha; Febri Ariyantiningsih (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The purpose of the study was to determine the Effect of Service Quality, Timeliness of Service, and Environmental Comfort on Patient Trust through Inpatient Satisfaction at Asembagus Hospital as an Intervening Variable. The sampling technique used in this study was simple random sampling of 98 patients. Data analysis and hypothesis testing in this study used Structural Equation Model – Partial Least Square (PLS-SEM) The results showed that Service Quality has a significant positive effect on Patient Trust, Timeliness of service has a significant positive effect on Patient Trust, Environmental comfort has a significant positive effect on Patient Trust, Service Quality has a significant positive effect on Patient Satisfaction, Timeliness of service has a significant negative effect on Patient Satisfaction, Environmental comfort has a positive but not significant effect on Patient Trust, Patient Trust has a significant positive effect on Patient Satisfaction, Service Quality has a significant positive effect on Patient Satisfaction through Patient Trust, Timeliness of service has a significant positive effect on Patient Satisfaction through Patient Trust, Environmental comfort has a significant positive effect on Patient Satisfaction through Patient Trust